Gambaran Risiko Diabetes Melitus Gestasional (DMG) Pada Ibu Hamil Di Wilayah Kerja Puskesmas Cipayung Jawa Barat - Adriani, Nadia Silvi; Warida, Warida; Burhannudin, Burhannudin (Poltekkes Kemenkes Jambi, 2024)
Background: Gestational diabetes mellitus (GDM) is a glucose intolerance disorder that first occurs during pregnancy. The condition is usually diagnosed after the 20th week of pregnancy, with some patients recovering after a period of childbirth. Risk factors for GDM are age, body mass index, family history of DM, hormonal changes, and lifestyle. Temporary blood glucose is a laboratory examination as a screening in pregnant women to find out pregnant women who are at risk of GDM. Method: This study used a descriptive cross-sectional design with secondary data at Cipayung Health Center January-April 2024. Result: The results showed that out of 143 data of pregnant women who did GDS examination, there were 5 (3.5%) pregnant women with high GDS results who were at risk of GDM and 138 people (96.5%) were normal. In the maternal age group ≥35 years, there were 3 (2.1%) pregnant women with high GDS at risk of GDM. In maternal gestational age, 3 (2.1%) pregnant women in the 3rd trimester with high GDS were at risk of GDM. In BMI, as many as 3 people (2.1%) of pregnant women in the obese category have high GDS results at risk of GDM. Conclusion: Suggestions, especially for pregnant women, should be routine to always do ANC during pregnancy such as checking blood sugar and maintaining a healthy lifestyle so that blood sugar does not increase.